Gambaran Pengetahuan Ibu Hamil Trimester III Tentang Persalinan Kala I Memanjang Di Klinik Helen Tarigan Di Kota Medan Tahun 2021 - Nurhayani Purba (Information Technology and Science (ITScience), 2022)
First stage of labor is said to be prolonged if it has lasted more than 24 hours in primi and 18 hours in multistage I prolonged latent phase, the uterus tends to be in a hypertonic state, this can result in inadequate contractions and only mild (less than 15 mm Hg on the monitor screen), therefore uterine contractions are ineffective. This study aims to obtain a description of the knowledge of third trimester pregnant women about the first stage of lengthening at the Helen Tarigan Clinic in 2021.